BODIPY-Pyridylhydrazone Probe for Fluorescence Turn-On Detection of Fe3+ and Its Bioimaging Application - Jukkrit Nootem; Chanchai Sattayanon; Rathawat Daengngern; Anyanee Kamkaew; Worawat Wattanathana; Suttipong Wannapaiboon; Paitoon Rashatasakhon; Kantapat Chansaenpak (My University, 2021)
A novel pyridylhydrazone-tethered BODIPY (BODIPY-PH) was synthesized, fully characterized via nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopic (FTIR), and single-crystal X-ray diffraction (SC-XRD) techniques, and developed for the selective detection of Fe3+ through fluorescent enhancement process. This derivative showed 1:1 binding with Fe3+ in an acetonitrile-water mixture (1:9 v/v) with the binding constant (K) of 5.4 × 104 M−1 and the limit of detection of 0.58 µM. The Fe3+ complexation reaction has been proved to be a reversible process and could be effectively repeated up to three cycles. The electronic properties of BODIPY-PH and its Fe3+ complex modeled by the density functional theory (DFT) method suggested the presence of chelation-enhanced fluorescence (CHEF) effect in the Fe3+ binding reaction. The X-ray absorption spectroscopy (XAS) probed at Fe K-edge confirmed the complex formation between BODIPY-PH and the Fe3+ in an octahedral geometry. Finally, bioimaging against human embryonic kidney (Hek293) cell, through confocal fluorescence microscopic technique indicated that the BODIPY-PH displayed good permeability and low toxicity toward the tested cell lines and showed enhanced fluorescent signal in the cells incubated with Fe3+ proving its capability for Fe3+ analysis in cellular matrix.
Keywords: BODIPY; Binding constant; Proton NMR; Molecular Sensors and Ion Detection